Visualizing problem solving effects on student performance and problem-solving skills in chemistry - Florendo, Liezl Aquino (2007)
Chemistry as part of the science curriculum should be taught in a way that students find it easier, interesting and relevant. The purpose of this study was to investigate the effects of visualizing problem solving on the performance and problem solving skills of freshman college students in chemistry. It was conducted with 60 college freshmen of the Palawan State University as participants. The pretest-posttest control group design was used. Findings revealed that students exposed to visualizing problem solving instruction performed significantly better compared to those exposed to the lecture method. VPS strategy enhances students' problem solving skills in terms of collecting necessary information to solve the problem, strategy in solving problem specifically arriving at appropriate equations and performing necessary calculations.
"March 2007."
Thesis (M.A. Education : Chemistry Education)--University of the Philippines Diliman.
Keywords: Chemistry -- Study and teaching (Higher) -- Philippines -- Palawan; Problem solving -- Study and teaching (Higher) -- Philippines -- Palawan; College freshmen -- Philippines -- Palawan